High Temporal Resolution 3D Live-Cell Imaging of Budding Yeast Meiosis Defines Discontinuous Actin/Telomere-Mediated Chromosome Motion, Correlated Nuclear Envelope Deformation and Actin Filament Dynamics - Nozaki, Tadasu; Chang, Frederick; Weiner, Beth; Kleckner, Nancy (Frontiers in Cell and Developmental Biology, 2021)
Chromosome movement is prominent at mid-meiotic prophase and is proposed to enhance the efficiency and/or stringency of homolog pairing and/or to help prevent or resolve topological entanglements. Here, we combine fluorescent repressor operator system (FROS) labeling with three-dimensional (3D) live-cell imaging at high temporal resolution to define the detailed kinetics of mid-meiotic prophase motion for a single telomere-proximal locus in budding yeast. Visual inspection of 3D images taken at 500 ms intervals reveals three qualitatively different motion "phenotypes": "straight", in which the telomere moves very rapidly in a straight or curvilinear path; "pauses", in which the telomere jiggles in place, as in premeiotic cells; and "directed", in which telomere movement is directional but zig-zag in nature and slower than during "straight" motion. Telomeres remain nuclear envelope-associated throughout, and straight motions can be accompanied by elongation of the nuclear shape, nucleated at the point of telomere association. Integration with earlier findings suggests that the critical event for mid-meiotic prophase chromosome dynamics is sporadic, transient movement telomere/Linker of Nucleoskeleton and Cytoskeleton (LINC) complexes along actin filaments mediated by myosin motor protein Myo2, manifested here as "straight" motion. Notably these straight movements are very transient (~2 s duration). We speculate that resistance from the associated nuclear envelope limits the duration/track length of Myo2-mediated telomere movement. Directed movement likely occurs primarily as an indirect consequence of motion driven by another telomere, perhaps as an effect of nuclear envelope deformation. Overall, the biological consequences of motion for chromosome function can be attributed to sequential and simultaneous events of this nature as nucleated at different telomeres. The presented methodology and findings provide opportunities for future exploration of these and other phenomena.